Proposal for a budget in the setting up of The Indigenous Malaysian Heritage Village for Architectural Heritage Studies for the Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia - Mohd Nawawi, Norwina ([s.n.], 2001)
A working paper to request fund to set up an indigenous village within the compound of IIUM Gombak campus for purpose of conservation and studies on heritage buildings of Malaysia.